FROM EPIDEMIOLOGICAL EVIDENCE TO THE CLASSROOM: HPV, SCIENTIFIC LITERACY AND INEQUALITIES IN HEALTH EDUCATION - Sheila Matos Viana Soares Barreto; Sabrina Mendes Couto; Diana Matos Viana Soares Almeida; Hiago Silva Santos; Ita de Oliveira e Silva (Artefactum - revista de estudos interdisciplinares, 2026)
Human papillomavirus (HPV) often enters school in a fragmented way: as a virology topic, a vaccination campaign or a sensitive issue related to sexuality. This article analyses how bringing these dimensions together can strengthen scientific literacy and health education among adolescents. A critical narrative review was conducted through a targeted search of PubMed/MEDLINE, SciELO, LILACS and ERIC, updated on 17 August 2026. The analytical corpus comprised 25 peer-reviewed articles and six official or institutional documents published between 2005 and 2026. Brazilian studies on knowledge, vaccination, school-based interventions and population impact were prioritised, together with broader reviews and educational references. The literature shows that educational activities tend to improve knowledge, but greater knowledge does not automatically lead to vaccination when family, access, consent, professional recommendation and service organisation remain as barriers. These obstacles are unequally distributed and particularly affect boys, public-school students, adolescents in the Northeast and families with lower income or educational attainment. By connecting pre-vaccination evidence from Southern Bahia with national findings on reductions in vaccine-targeted genotypes, CIN3 and cervical cancer, the review shows how HPV can be used to teach biological concepts, evidence appraisal and the social distribution of scientific benefits. Schools have a distinct role in this process: enabling students to understand evidence, discuss prevention without moralising sexuality and recognise the material conditions that shape health decisions.